Pengaruh Perceived Usefulness dan Perceived Ease Of Use Terhadap Keputusan Pembelian Menggunakan Go-Pay - Steven John Wibowo; Tinton Ramadhan (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to know and to analyze the influence of perceived usefulness and perceived ease of use on purchasing decisions using Go-pay at Warteg Uun Taman Galaxy. This research uses quantitative methods through questionnaire survey with non-probability sampling method. This questionnaire was distributed to 100 respondents who were processed using SPSS. Hypothesis test results (t test), perceived usefulness effect on purchasing decisions with t count 3.986> t table 1.984. Perceived Ease of use has an effect on purchasing decisions with t count 2.725> t table 1.984. The coefficient of determination is 50%. The implication of this research is that Warteg Uun pays more attention to perceived usefulness, and perceived ease of use in the use of Go-pay as a payment medium.